Outcome of a Low-Cost Glaucoma Implant versus the Baerveldt Glaucoma Implant for Paediatric Glaucoma in a Tertiary Hospital in Egypt - Mahmoud F. Rateb; Hazem Abdel Motaal; Mohamed Shehata; Mohamed Anwar; Dalia Tohamy; Mohamed G. A. Saleh (Journal of Ophthalmology)
Purpose. To compare safety and efficacy between a low-cost glaucoma drainage device (GDD), the Aurolab aqueous drainage implant (AADI), and the Baerveldt glaucoma implant (BGI) in refractory childhood glaucoma in Egypt. Methods. This is a retrospective study of patients who received either an AADI or BGI at a tertiary care postgraduate teaching institute. Children aged <16 years with uncontrolled intraocular pressure (IOP) with or without prior failed trabeculectomy who completed a minimum 6-month follow-up were included. The outcome measures were IOP reduction from preoperative values and postoperative complications. Results. Charts of 57 children (younger than 16 years old) diagnosed with refractory childhood glaucoma were included. Of these, 27 eyes received AADI implants (group A), while 30 received BGI implants (group B). The mean preoperative baseline IOP was 34 ± 5 mmHg in group A versus 29 ± 2 mmHg in group B (p=0.78) in patients on maximum allowed glaucoma medications. In group A versus group B, the mean IOP decreased to 13.25 ± 8.74 mmHg (p=0.6), 12.8 ± 5.4 mmHg (p=0.7), and 12.6 ± 5.6 mmHg (p=0.9) after 1 week, 3 months, and 6 months, respectively. However, in group A, an anterior chamber reaction appeared around the tube in 14 cases starting from the first month and resolved with treatment in only 4 cases. In the other 10 cases, the reaction became more severe and required surgical intervention. This complication was not observed in any eye in group B. Conclusion. AADI, a low-cost glaucoma implant, is effective in lowering IOP in patients with recalcitrant paediatric glaucoma. However, an intense inflammatory reaction with serious consequences developed in some of our patients; we believe these events are related to the valve material. We therefore strongly recommend against its use in children.